2011
DOI: 10.1103/physreva.83.032714
|View full text |Cite
|
Sign up to set email alerts
|

Chemical pathways in ultracold reactions of SrF molecules

Abstract: We present a theoretical investigation of the chemical reaction SrF + SrF $\rightarrow$ products, focusing on reactions at ultralow temperatures. We find that bond swapping, SrF + SrF $\rightarrow$ Sr$_2$ + F$_2$, is energetically forbidden at these temperatures. Rather, the only energetically allowed reaction is SrF + SrF $\rightarrow$ SrF$_2$ + Sr, and even then only singlet states of the SrF$_2$ trimer can form. A calculation along a reduced reaction path demonstrates that this abstraction reaction is barri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 42 publications
3
34
2
Order By: Relevance
“…(14)] of both components |M L | = 0,1 at ultracold temperature are the same in the van der Waals regime and are dictated by a d 6 dependence in the electric regime [Eqs. (16) and (18)] with different magnitudes. These expressions provide a clear explanation of the trends observed numerically.…”
Section: Qt Model For P-wave Collisionsmentioning
confidence: 99%
“…(14)] of both components |M L | = 0,1 at ultracold temperature are the same in the van der Waals regime and are dictated by a d 6 dependence in the electric regime [Eqs. (16) and (18)] with different magnitudes. These expressions provide a clear explanation of the trends observed numerically.…”
Section: Qt Model For P-wave Collisionsmentioning
confidence: 99%
“…To proceed to ultracold temperatures would require evaporative cooling, whereby the highestenergy molecules are siphoned off and the remainder come to thermal equilibrium via elastic collisions. But this procedure comes with a catch: if the molecules are reactive, e.g., by the reaction 2 SrF → SrF 2 + Sr [11], then they may be lost to this reaction before coming into thermal equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…At shorter ranges, the quantum statistics and chemical nature of the specific species comes to the forefront [4,14]. Polar radicals behave in even richer fashions: topological crystals [15], half-integer vortices generated by conical intersections [16], and spin-dependent chemistry [17] have been predicted, and the utility of using magnetic fields to trap radicals while performing electricdipole-dependent studies has already been demonstrated [14,18,19]. Motivated by these predictions, several groups are pursuing the production of ultracold radicals such as RbSr [19,20] and LiYb [21].…”
mentioning
confidence: 99%